Adaptation of utilization of new normal era E-digital application at Reza and Palekko Cafe in Pare-Pare - Abdi, Abdi (Technium: Romanian Journal of Applied Sciences and Technology, 2021)
The use of technology is a solution to increase food and beverage sales. A technology called digital application develops sales activities to become all digital. This study aims: To find out what types of digital applications are used at Cafe Reza and Palekko in Pare-Pare. To find out how the implementation and effectiveness of digital applications in increasing food and beverage sales in the new normal era at Reza and Palekko Cafes in Pare-Pare. Data collection from this study was taken by the following techniques: interviews and documentation and data analysis was carried out using a qualitative descriptive method. The results of this study indicate that the type of digital application used by Reza and Palekko Cafes to increase food and beverage sales in the new normal era is the mokapos.com application, the implementation of the mokapos digital application has a positive impact and extraordinary effectiveness for Reza and Palekko cafes because in addition to simplifying the stages stages of employee performance, the integrated mokapos application with grabfood, gofood, go-pay greatly supports the increase in food and beverages at Reza and Palekko cafes in this new normal era.